WHEAT STRAW CONVERSION BY ENZYMATIC SYSTEM OF GANODERMA LUCIDUM - Mirjana Stajic; Biljana Kukavica; Jelena Vukojevic; Jasmina Simonic; Sonja Veljovic-Jovanovic (BioResources, 2010)
The purpose of this study was to resolve the question of whether various nitrogen sources and concentrations affect characteristics of selected G. lucidum ligninolytic enzymes participating in wheat straw fermentation. This is the first study reporting the presence of versatile peroxidase activity in crude extract of G. lucidum culture, as well as isoforms profile of Mn-oxidizing peroxidases. NH4NO3 was the optimum nitrogen source for laccase and Mn-dependent peroxidase activity, while peptone was the optimum one for versatile peroxidase activity. Four bands with laccase activity were obtained by native PAGE and IEF separations from medium enriched with inorganic nitrogen source, and only two bands from medium containing organic source. Medium composition was not shown to affect isoenzyme patterns of Mn-oxidizing peroxidases. Four isoforms of Mn-dependent peroxidase and three of versatile peroxidase were obtained on native PAGE. By IEF separation, five isoforms of Mn-dependent peroxidase and only two of versatile peroxidase were observed. The results demonstrated that G. lucidum has potential for mineralization and transformation of various agricultural residues and should take more significant participation in large-scale biotechnological processes.